Muayene ve Teşhis: Ağız İçi Muayene, Ağız Dışı Muayene, Yansıyan Ağrılar - NALCI, GAMZE; Nalcı G. (Türkiye Klinikleri, 2022)
İyi ve doğru bir tedavi ancak kesin bir teşhis ile mümkündür. Başarılı bir endodontik tedavi için öncelikle eksiksiz anamnez almak ve etraflıca muayene yapmak şarttır. Objektif muayene ektraoral ve intraoral dokuların detaylı incelenmesini, herhangi bir patoloji varlığı ya da yokluğu açısından değerlendirilmesini içerir.

A correct treatment is only possible with a definite diagnosis. For a successful endodontic treatment, it is essential to take a complete anamnesis and perform a thorough examination. Objective examination includes detailed examination of extraoral and intraoral tissues and evaluation for the presence or absence of any pathology.
Keywords: Diş Hekimliği; Klinik Bilimler; Endodonti; Sağlık Bilimleri; Dentistry; Clinical Sciences; Endodontics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry